2015
DOI: 10.1175/jtech-d-15-0029.1
|View full text |Cite
|
Sign up to set email alerts
|

Biofouling Effects on the Response of a Wave Measurement Buoy in Deep Water

Abstract: The effects of biofouling on a wave measurement buoy are examined using concurrent data collected with two Datawell Waveriders at Ocean Station P: one heavily biofouled at the end of a 26-month deployment, the other newly deployed and clean. The effects are limited to the high-frequency response of the buoy and are correctly diagnosed with the spectral “check factors” that compare horizontal and vertical displacements. A simple prediction for the progressive change in frequency response during biofouling repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…These changes significantly increased buoyancy and surface following ability. The heave response frequency (Thomson et al, ), the highest frequency the buoy is expected to closely follow the sea surface, was estimated to be 3.80 Hz, well above the highest frequency of interest. k e is a simple combination of auto‐spectra.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…These changes significantly increased buoyancy and surface following ability. The heave response frequency (Thomson et al, ), the highest frequency the buoy is expected to closely follow the sea surface, was estimated to be 3.80 Hz, well above the highest frequency of interest. k e is a simple combination of auto‐spectra.…”
Section: Methodsmentioning
confidence: 97%
“…Specifically, we assume that buoy perfectly responds to the heave and slope of the sea surface, i.e., response amplitude operators = 1 (e.g., Masson & LeBlond, ), over the frequency range 0.05–0.50 Hz. When the buoy response is perfect, deviations of k e from the open water relation can be used as a quality control measure and as a flag for buoy response to currents, mooring forces, and bio‐fouling (Thomson et al, ; Tucker, ; Tucker & Pitt, ). In the absence of these effects and in the presence of ice, deviations of k e / k ow from 1 can be interpreted as the modification of waves due to ice.…”
Section: Methodsmentioning
confidence: 99%
“…The shape differences resulted in very different icing conditions. Changes of hydrodynamic response of buoys can alter the frequency response of a buoy, as studied in a biofouling case (Thomson et al, ). Without a thorough study of sources of the observed discrepancies between these two types of buoys, reliable cross‐calibration cannot be performed.…”
Section: The Measured Wave Characteristicsmentioning
confidence: 99%
“…In addition, the fluid structure interactions of a wave buoy can linearize the wave time series (James, ; Magnusson et al, ). Wave buoys are also subject to biofouling (Thomson et al, ), vandalism (Beets et al, ), and affected by tidal currents. These drawbacks in sampling using wave buoys are mitigated by the unparalleled spatial distribution, length of record, and consistency of continuous surface elevation measurement by the Datawell Waverider buoys (Casas‐Prat & Holthuijsen, ).…”
Section: Data Setmentioning
confidence: 99%